CUSTOMER-BASED BRAND EQUITY OF RETAIL BANKS IN VIETNAM - Vũ Minh Tú (Tạp chí Khoa học Đại học Đà Lạt)
Developing customer-based brand equity (CBBE) for retail banks in Vietnam is still questionable, and the subject has not been properly investigated due to the fact that Vietnam is a young developing country. To extend a study of CBBE to Vietnam, this research conducts a survey to interview 157 respondents who are customers of one or more banks. Based on Exploratory Factor Analysis and a Structural Equation Model (SEM), findings confirm that there are significant relationships between satisfaction, quality, and uniqueness, meaning that an increase in perceived quality causes a rise in brand satisfaction. Similarly, an increase in brand uniqueness increases brand satisfaction. Brand satisfaction significantly enhances brand loyalty, while perceived quality and brand uniqueness have indirect effects on brand loyalty. As a result, this paper suggests that perceived quality and brand uniqueness must be formed before brand satisfaction in order to enhance brand loyalty. Furthermore, the direct effects of perceived quality and brand uniqueness on brand loyalty are lower than their indirect influences on brand loyalty via brand satisfaction.